Analysis of a Standardized Perioperative Pain Management Order Set in Highly Opioid-Tolerant Patients. Issue 2 (June 2019) - Isaacs, Alex N.; Knight, Kellie L.; Nisly, Sarah A.
Abstract : Objective: The aim was to assess a standardized order set for perioperative pain management in highly opioid-tolerant patients undergoing elective orthopedic surgery. Methods: This retrospective chart review evaluated a pain order set in highly opioid-tolerant patients undergoing elective total knee or total hip arthroplasty from January 2010 through August 2012. Based on the date of the surgery, patients were allocated into preimplementation or postimplementation order set groups. The primary outcome assessed whether an adjustment in daily opioid dosage was required within the first 48 hours postoperatively. Secondary outcomes included pain scores, length of hospitalization, and safety outcomes. Results: Sixty patients were included in the analysis. An adjustment to postoperative opioid therapy occurred in 62% of the patients in the preimplementation group and in 56% of postimplementation group patients ( P = 0.786). There were no differences in median pain scores 48 hours postoperatively ( P = 0.348). Cumulative toxicity was increased after order set implementation compared with previous patients (44% versus 5%, P < 0.005); however, opioid doses held for sedation was the only individual toxicity to reach statistical significance ( P = 0.011). Conclusions: This study is the first to evaluate a standardized order set for pain management in highly opioid-tolerant patients undergoing elective orthopedic surgery. The order set demonstrated similar efficacy to previous treatment modalities, but opioid-induced sedation was of concern with the order set. After the initial analysis, the order set was modified to minimize opioid-induced sedation. Continual safety analysis is warranted for quality improvement to enhance perioperative pain management in highly opioid-tolerant patients. Abstract : Supplemental digital content is available in the text.